TEMPERATURE AS SOURCE DOMAIN OF METAPHORICAL EXPRESSIONS: A Conceptual Metaphor Analysis to Novel Answered Prayers By Sydney Sheldon - Muhammad Adam (Prologue: Journal on Language and Literature, 2017)
This research is the study of metaphorical expressions of temperature terms used as source domain. Researcher takes dialogs and narratives in the novel Answered Prayers by Sydney Sheldon as data source. Qualitativedescriptive research is used by collecting metaphorical expression whichused temperature terms as source domain based on the conceptualmetaphor theory. Researcher finds that there are four target domains ofmetaphorical expressions using temperature terms; they are affection,emotional intensity, personality and physical appearance (related to afashionable appearance). From those four target domains, the highestnumber is the conceptual metaphor of AFFECTION is TEMPERATUREwith 23 metaphorical expressions. It also appears in this research thathuman’s experiential basis to temperature influence the terms used inmetaphorical expressions.